High-intensity frequency ultrasound: Noninvasive targeted therapy, the new vogue in globus treatment of benign and cancerous solid tumors and rejuvenation procedures (Journal of Obstetrics and Gynaecology of Eastern and Central Africa, 2024)
Background: High-intensity frequency ultrasound (HIFU), a noninvasive ultrasound beam is focused onan exact tissue area that requires treatment. The highly focused energy from ultrasound causes thetemperature of the tissue to rise, and the heat ablates the targeted tissue area. This therapy is gainingpopularity and momentum globally for treating of brain, breast, prostate, thyroid, liver, kidney, bonetumors, fibroids, adenomyosis, and endometriosis. Additionally, it is used in placenta accreta syndromeand cesarean scar pregnancy. Cosmetics include rejuvenation of connective tissue on the face andvulva. Exploration of uses for the treatment of postpartum hemorrhage and cervical cancer is underway.Methods: An orientation meeting was held among Kenyatta National Hospital and the University ofNairobi multidisciplinary clinical and administrative personnel. This was followed by a study tour to Chinathat engaged academia, researchers, clinicians, and radiologists to gain a first-hand understanding of theinvention process, setup for procedures, and innovative applications of HIFU in both private and publichealth institutions.Results: Promising success data are generated in high-income counties. Recently introduced in WestAfrica with the possibility of introduction in Eastern Africa.Conclusion: Noninvasive targeted therapies are the new vogue, and there seems to be a globusapplication for HIFU. Acquisition of this technology, addressing the normative environment, competenciesof multidisciplinary HCP, and research are needed in low- and middle-income countries. This noveltechnology can be cost-effective for the health system and improve patients’ experience. Furthermore, acombination of machine learning and clinical radiological imaging can be used as a predictor of tumorregrowth potential.